Groundwater-level fluctuation effects on petroleum hydrocarbons in vadose zones and their potential risks: Laboratory studies - An, Seongnam; Kim, Sang Hyun; Woo, Heesoo; Choi, Jae woo; Yun, Seong-Taek; Chung, Jaeshik; Lee, Seunghak (Elsevier BV, 2024)
Despite the role of the vadose zone protecting groundwater from contamination, the non-stationarity in this zone makes it difficult to predict the behavior of petroleum hydrocarbons (PH) therein. In laboratory soil columns with sandy and sandy loam soils, we simulated a vadose zone subjected to repeated groundwater-level fluctuation (GLF) to evaluate the behavior of PH under hydrodynamic conditions. The GLF vertically redistributed the PH, the extent of which was pronounced in the sandy soil with a high initial concentration due to the enhanced transport of the immiscible PH through the larger pores. The frequency of GLF did not show a substantial effect on the extent of PH redistribution but largely affected their attenuation. The greater GLF hindered PH volatilization by maintaining a high degree of water saturation, while the subsequent development of a local anaerobic regime inhibited biodegradation, which was more apparent in the sandy loam. Finally, a specific potential risk index was introduced to quantitatively compare the potential risk of PH contamination in different vadose zones exposed to GLF. Overall, the sandy soil contaminated with the higher total PH (TPH) concentration showed markedly higher potential risk indices (i.e., 18.4？29.0%), while the ones comprised of the sandy loam showed 0.6？4.9%, which increased under the greater number of GLF cycles.